2021
DOI: 10.1371/journal.pone.0260660
|View full text |Cite
|
Sign up to set email alerts
|

Selection and validation of reference genes for normalization of qRT-PCR data to study the cannabinoid pathway genes in industrial hemp

Abstract: There has been significant interest in researching the pharmaceutical applications of Industrial hemp since its legalization three years ago. The crop is mostly dioecious and known for its production of phytocannabinoids, flavonoids, and terpenes. Although many scientific reports have showed gene expression analysis of hemp through OMICs approaches, unreliable reference genes for normalization of qRT-PCR data make it difficult to validate the OMICs data. Four software packages: geNorm, NormFinder, BestKeeper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…The gene expression of two cannabinoid pathway genes, CBDAS and THCAS was measured using qRT-PCR (Deguchi et al, 2021 ). Since the CBDAS and THCAS genes have more than 90% homology in their sequences, both sequences were aligned, and a variable region was used to design qRT-PCR primers to avoid off-target effects between them.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene expression of two cannabinoid pathway genes, CBDAS and THCAS was measured using qRT-PCR (Deguchi et al, 2021 ). Since the CBDAS and THCAS genes have more than 90% homology in their sequences, both sequences were aligned, and a variable region was used to design qRT-PCR primers to avoid off-target effects between them.…”
Section: Methodsmentioning
confidence: 99%
“…The elongation factor 1-α gene was used as a reference gene (Fw: 5'- GCCCTGTCTTTGAGAGCAAC-3', Rv: 5'-CAATCCACTGCTCAATGTGG-3'). Relative gene expression levels of CBDAS and THCAS were calculated using the 2 −ΔΔCt method (Deguchi et al, 2021 ). Statistical analysis was performed using a 1-way ANOVA with Tukey's multiple comparison test (α = 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…Two olivetolic acid cyclase genes ( CsAOC-1 and CsAOC-2 ) and seven prenyltransferase -like genes (LOC115713185, LOC115707809, LOC115713148, LOC115713171, LOC115713205, LOC115713215, and LOC115722991) were identified in the CBDRx reference genome (GenBank GCF_900626175.2), but CsPT4 (LOC115713185) was selected for this study as it was the only one found functional in transgenic yeast ( Luo et al., 2019 ). Amplification of three reference genes, Elongation factor 1 alpha , Serine/threonine-protein phosphatase and Tubulin α -1 ( Guo et al., 2018 ; Deguchi et al., 2021 ), selected based on their stability in C. sativa , was used as an internal control for normalizing the relative expression data. Primer efficiencies were tested by comparison against a standard curve for each gene.…”
Section: Methodsmentioning
confidence: 99%
“…XM_030654744.1)-for C. sativa were selected according to Deguchi et al (2021), checked in each cDNA using the quantitative PCR quantifcation (qPCR) and analysed with Visual basic application for Excel (GeNorm) that automatically calculates the gene stability (Vandesompele et al 2002). 18S ribosomal RNA (18S) was then selected as the reference gene for the standardisation.…”
Section: Pip Genes Expressionmentioning
confidence: 99%